Risk Factors for the Development of Cancers (Kindle, 2023)
Multiple risk factors are for all types of cancers. These include endogenous factors and exogenous factors. The main constitutional and environmental risk factors are well clarified, but it remains unknown how they interact to contribute to the development of different cancers. Several relative risk factors may serve as important prognostic factors for the malignancies. Therefore, clinicians must appreciate the significance of taking a detailed patient history, including a social, family, and work history. A discussion of the most prevalent risk factors follows; however, it is not exhaustive. Therefore, in this book we aimed to summarize the main risk factors of each cancer.
Keywords: Cancer Risk Factors; Cancer Etiology; Genetic Risk Factors; Cancer Prevention